Online Information-Seeking Behaviors of Parents of Children With ADHD. (January 2018) - Sage, Adam; Carpenter, Delesha; Sayner, Robyn; Thomas, Kathleen; Mann, Larry; Sulzer, Sandy; Sandler, Adrian; Sleath, Betsy
This article describes ( a ) parent questions about ADHD (attention deficit/hyperactivity disorder), ( b ) parent Internet use to seek ADHD information, and ( c ) associations between type of Internet access and ADHD information-seeking. Seventy parents of children (ages 7-17 years) with ADHD completed questionnaires after their child's visit with their pediatrician. Bivariate relationships were assessed using chi-square statistics, Pearson correlation coefficients, or t tests. Parents identified an average of 8.9 questions about ADHD for their child's provider. Common questions were related to medication and long-term implications of ADHD. A majority of parents searched the Internet for general ADHD information (87%) and ADHD medication information (81%). White parents accessed the Internet significantly more via home computer, mobile phone, and tablet, and significantly less via public library than non-White parents. Parents who accessed the Internet via home computers and tablets were more likely to search the Internet for ADHD medication information than parents who did not.